2019
DOI: 10.1038/s41416-019-0465-y
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption by type and risk of digestive cancer: a large prospective cohort study

Abstract: Background Evidence of a protective effect of coffee consumption for liver cancer has been found but inconclusive for other digestive cancers. Few previous studies have investigated coffee type (specifically instant or ground coffee) and few investigated a range of digestive cancer types within the one cohort. We therefore investigated the association between coffee consumption by type with digestive cancers in a large UK population-based cohort. Methods We analysed data from the UK Biobank cohort study using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…A total of 11 cohort studies were selected as the primary subjects (Hiatt et al, 1988;Shibata et al, 1994;Harnack et al, 1997;Michaud et al, 2001;Isaksson et al, 2002;Stolzenberg-Solomon et al, 2002;Luo et al, 2007;Nilsson et al, 2010;Bhoo-Pathy et al, 2013;Bidel et al, 2013;Guertin et al, 2015). From 285 papers by citing these 11 articles, four studies among them were additionally secured as the secondary subjects (Genkinger et al, 2012;Lukic et al, 2018;Tran et al, 2019;Zhou et al, 2019). And there was not any new cohort study meeting the selection criteria on the reference in the primary and secondary study subjects.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 cohort studies were selected as the primary subjects (Hiatt et al, 1988;Shibata et al, 1994;Harnack et al, 1997;Michaud et al, 2001;Isaksson et al, 2002;Stolzenberg-Solomon et al, 2002;Luo et al, 2007;Nilsson et al, 2010;Bhoo-Pathy et al, 2013;Bidel et al, 2013;Guertin et al, 2015). From 285 papers by citing these 11 articles, four studies among them were additionally secured as the secondary subjects (Genkinger et al, 2012;Lukic et al, 2018;Tran et al, 2019;Zhou et al, 2019). And there was not any new cohort study meeting the selection criteria on the reference in the primary and secondary study subjects.…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike most cohort studies, UK Biobank participants reported whether they typically consumed decaffeinated, instant, ground or other types of coffee. In this way, Tran et al 5 provide an important methodological advance over previous studies.…”
Section: Mainmentioning
confidence: 93%
“…In line with earlier studies, they found that coffee drinking was associated with a lower risk of hepatocellular carcinoma (HCC), the most common type of primary liver cancer, although associations with other types were largely null. Importantly, Tran et al 5 found no evidence that the inverse association between coffee drinking and HCC varied by coffee type. Despite small case numbers, these results are consistent with a few prior studies that evaluated brewing type, such as in the ATBC study of Finnish smokers, where inverse associations for coffee drinking with incident liver cancer were observed for both boiled and filtered coffee.…”
Section: Mainmentioning
confidence: 98%
See 2 more Smart Citations